Pelatihan Sistem Informasi Berbasis Geopasial Bagi Siswa Jurusan Geomatika SMKN 3 Selong - Apriyeni, Baiq Ahda Razula; Supriadi, Herman; Hidayat, Muh. Adrian Juniarta; Hidayat, M. Adnan; Liana (Universitas Triatma Mulya, 2025)
The use of information technology, especially geospatial-based information systems, has become very important in various sectors of life. This is especially relevant in the context of education, where understanding and mastery of technology is key to preparing the younger generation to face the complex challenges of the job market. This geospatial-based information system training, we aim to be able to create a young generation who are not only skilled and competent, but also innovative in facing future challenges. The implementation of geospatial-based information system training activities are strategies that will be used to convey material, develop skills, and facilitate the understanding of trainees about the concepts taught in geospatial and geomatics spatial planning. However, the knowledge of students, especially vocational school students who have a Geomatics major, is limited. For this reason, this study provides additional knowledge of students about Geomatics. Some of the methods used in the implementation of this training activity include using methods: initial activities, process activities and final activities. In the initial stage and the last, students are given the same questionnaire. The data results show an increase in student answers regarding the geomatics major. The main indicator that is a reference is the quantity and quality of students' answers that have increased. Previously they could mention one or two answers, after attending training and career development their answers increased and became more completeThe use of information technology, especially geospatial-based information systems, has become very important in various sectors of life. This is especially relevant in the context of education, where understanding and mastery of technology is key to preparing the younger generation to face the complex challenges of the job market. This geospatial-based information system training, we aim to be able to create a young generation who are not only skilled and competent, but also innovative in facing future challenges. The implementation of geospatial-based information system training activities are strategies that will be used to convey material, develop skills, and facilitate the understanding of trainees about the concepts taught in geospatial and geomatics spatial planning. However, the knowledge of students, especially vocational school students who have a Geomatics major, is limited. For this reason, this study provides additional knowledge of students about Geomatics. Some of the methods used in the implementation of this training activity include using methods: initial activities, process activities and final activities. In the initial stage and the last, students are given the same questionnaire. The data results show an increase in student answers regarding the geomatics major. The main indicator that is a reference is the quantity and quality of students' answers that have increased. Previously they could mention one or two answers, after attending training and career development their answers increased and became more complete.